A pilot study of scleral thickness in central serous chorioretinopathy using anterior segment optical coherence tomography - Yun Ji Lee (Nature Portfolio, 2021)
Abstract The aim of this study is to compare the scleral thickness of central serous chorioretinopathy (CSC) eyes with controls using anterior segment optical coherence tomography (AS OCT). This prospective case control study included 15 patients (15 eyes) with CSC and 15 age and gender matched healthy subjects. All subjects underwent spectral domain OCT with enhanced depth imaging and swept source AS OCT of temporal sclera. We investigated difference in scleral thickness between the two groups and relationship between choroidal and scleral thickness. Among the 15 eyes in the study group, 1 eye had acute CSC, 4 had recurrent CSC, 7 had inactive CSC, and 3 had chronic CSC. There was no significant difference in terms of age, gender, axial length and spherical equivalent between the two groups. The choroidal and scleral thickness of the study group were significantly greater than those of the control group (P < 0.001, P = 0.034). Choroidal thickness was positively correlated with scleral thickness (P = 0.031). A thick sclera along with a thick choroid were demonstrated in CSC eyes using AS OCT. Scleral characteristics might be involved in the pathogenesis of CSC by affecting outflow resistance of venous drainage in choroidal circulation.